Analisis Efisiensi Penggunaan Modal Kerja Pada Pt. Holcim Indonesia Tbk. - Aliah Pratiwi; Nurhayati; Latifah Chaeranil Hadiyati (CV Edujavare Publishing, 2023)
Effective working capital management is crucial for the success and long-term sustainability of manufacturing companies. This study focuses on analyzing the financial performance of PT. Holcim Indonesia Tbk, a leading cement manufacturer, over a ten-year period (2012-2021). The analysis includes key financial ratios such as Working Capital Turnover, Receivable Turnover, Quick Ratio, and Current Ratio to assess the company's efficiency in managing its working capital. The findings reveal that PT. Holcim Indonesia Tbk exhibited fluctuating results in its financial performance during the studied period. The Working Capital Turnover indicated inefficiency in capital utilization in some years, emphasizing the need for further review. On the other hand, the Receivable Turnover demonstrated consistently good performance in managing accounts receivable. Furthermore, the Quick Ratio and Current Ratio indicated favorable liquidity positions, suggesting the company's ability to meet its short-term financial obligations effectively. These ratios play a vital role in ensuring the company's financial stability and ability to generate profits in the long term. The study's statistical analysis, including one-sample t-tests, confirmed the findings, supporting the conclusion that PT. Holcim Indonesia Tbk's financial performance was generally satisfactory, with some areas needing improvement. Overall, this research provides valuable insights for the company's financial management and decision-making processes, contributing to its long-term success in a challenging industry.